Ethical and social insights into synthetic biology: predicting research fronts in the post-COVID-19 era - Wang, Gaofeng; Kong, Qingqing; Wang, Dong; Asmi, Fahad (Frontiers in Bioengineering and Biotechnology, 2023)
As a revolutionary biological science and technology, synthetic biology (SynBio) has already spread its influence from natural science to philosophy and social sciences by introducing biosafety, biosecurity, and environmental and ethical issues to society. The current study aims to elaborate the intellectual bases and research front of the synthetic biology field in the sphere of humanities and social sciences with knowledge mapping and bibliometric methods. The literature records from the Social Sciences Citation Index (SSCI) and Arts & Humanities Citation Index (A&HCI) in the Web of Science Core Collection from 1982 to 2021 were collected and analyzed to illustrate the intellectual structure of humanities and social research of SynBio. This study profiled the hotspots of research focus on its governance, philosophical and ethical concerns, and relevant technologies. This study offers clues and enlightenment for the stakeholders and researchers to follow the progress of this emerging discipline and technology and to understand the cutting-edge ideas and future form of this field, which takes on greater significance in the post-COVID-19 era.